Never Let a Crisis Go to Waste: Recruiting the Next Generation of Infectious Diseases Physicians - Curtis J. Donskey (Case Western Reserve University, 2017)
Sometimes infectious diseases can seem to be the least interesting subspecialty of internal medicine. We don't offer lifesaving or pain-relieving procedures. We offer the same advice over and over again hoping someday it might stick: wash your hands; stop prescribing antibiotics when there is no evidence of infection; and take your flu shot-it really won't give you the flu. We give advice that some consider expendable. Shouldn't all physicians be able to prescribe antibiotics with a little help from an online textbook or computer app? On top of all that, we apparently aren't very stylish. One of my female colleagues recently told me she can pick out all of the male infectious disease physicians at scientific meetings by the standard uniform of ill-fitting khakis and button-down shirts. But a new crisis is always lurking to remind us that infectious diseases can be one of the most interesting and challenging areas of medicine. Emerging infections-often exotic and frightening-grab the attention of everyone from frontline personnel to the news media: Legionnaires' disease; HIV; West Nile virus; SARS; MERS; chikungunya; Ebola virus; Zika virus; and Mycobacterium chimaera to name just a few. Without warning, common pathogens create havoc when they acquire new resistance mechanisms or virulence factors: multidrug-resistant gram-negative bacilli; Staphylococcus aureus; and Clostridium difficile. Standard procedures such as transrectal biopsy of the prostate and endoscopic retrograde cholangiopancreatography suddenly become risky due to increasing antimicrobial resistance or inadequate methods for device reprocessing.